Reflections on and suggestions for reporting vulnerability research: How can peer reviewed articles reflect complex practice in low consensus fields such that they better support review and synthesis?. Issue 97 (July 2019) - Tamás, Peter A.; Delaney, Aogán; Crane, Todd; Hengeveld, Geerten M.
Highlights: Generalized knowledge claims are required to meaningfully support policy. Generalized knowledge claims arise from synthesis across reports of studies. The way interdisciplinary studies are typically reported undermines synthesis. Existing reporting formats should be improved and a better format created. Abstract: As the international community increases investment in agricultural adaptation to climate change in low and middle-income countries (LMICs), there is increasing demand to extract generalized knowledge claims about vulnerability from individual studies. If synthesis is to successfully produce sound generalized knowledge claims, relevant evidence must be possible to find and interpret. The format through which research in this field is now normally reported does not adequately support finding relevant evidence nor its interpretation. This opinion piece outlines and assesses three possible pathways for changing reporting practices in vulnerability research – standardization of methods, reporting checklists, and modularised reporting – in order to support the identification and synthesis of evidence. Rather than resolving these issues, this piece intends to open up the conversation about them.